A comparative study of platelet to lymphocyte ratio as novel biomarker to predict severity and association with prognosis in COVID–19 patients - Mulla, Bahuddeen M.; Khan, Mumtaz A.; Krishnegowda, Ravi; Maddimani, Ramesh; C., Karthik; Khan, Naazim Javed (International Journal of Advances in Medicine, 2021)
Background: Influenza-like illness (ILI) and severe acute respiratory infection (SARI) are the important manifestations in day today clinical practice in COVID era. A number of clinical investigations including haematological parameters are used for the risk stratification of the patients. This study was undertaken in order to find the applicability of platelet to lymphocyte ratio in risk stratification. Methods: A prospective study was undertaken in Victoria hospital and Bowring and Lady Curzon hospitals attached to BMCRI tertiary care hospitals in Bangalore for a period of one and half years. All the patients were subjected for clinical and haematological evaluation and appropriate ratios were calculated. A total of 266 patients were enrolled in the study, out of which 144 were COVID negative and 122 were COVID positive. The data was analyzed using appropriate statistical methods using statistical package for social sciences (SPSS) version 24. Results: The mean age of the COVID negative patients was 43.37 years and COVID positive patient was 49.08 years. Males outnumbered females. There was statistically significant difference in mean platelet to lymphocyte ratio between the COVID positive and negative cases (226.4 versus 399.38). The area under curve was 0.614 for the platelet to lymphocyte ratio (PLR) in patients with severe and non-severe ILI and SARI cases. Majority of the haematological parameters were significantly different in SARI patients who were COVID positive and negative. Conclusions: PLR can be used as an indicator for risk stratification in ILI and SARI patients.